WORKSHOP PEMASARAN UBI LATA UNTUK PENINGKATAN EKONOMI MASYARAKAT LOKAL - Reny Nugraheni; Tri Ana Mulyati, Dianti Ias Oktaviasari, Fery Eko Pujiono (JOURNAL OF COMMUNITY DEDICATION, 2024)
Lata yam is one of the local commodities that has great potential to be developed as a superior product in the Badal Pandean Kediri area. Besides being rich in nutritional value, Lata yam has high flexibility to be processed into various value-added products, so that it can make a significant economic contribution to the local community. However, this potential has not been optimally utilised due to the community's limited understanding of marketing, especially digital marketing, which is now key in reaching a wider market and increasing the competitiveness of local products. This constraint has resulted in the low selling value of Lata yam and limited market reach, which in turn affects the income of farmers and small business actors in the region. Therefore, empowerment efforts are needed that can improve community marketing skills in processing and promoting Lata yam-based products. This community service programme aims to improve the marketing knowledge and skills of local communities through a Lata yam marketing workshop. This workshop includes training on basic marketing strategies, promotional content creation techniques, social media management, and simple digital marketing techniques that suit the capabilities and needs of the local community. The methods used included counselling, training, and intensive mentoring. Initial counselling focused on the importance of digital marketing for local products, followed by technical training in creating visual content and product descriptions that appeal to consumers. In addition, participants were taught how to manage social media such as Instagram and Facebook as effective yet cost-effective marketing tools. The results of this activity showed an increase in participants' understanding and skills in digital marketing. As many as 85% of participants who initially had not utilised social media for product marketing have now started to actively use the platform and demonstrated the ability to create more attractive and informative promotional content. In addition, there was an average sales increase of 15-20% in the three- month post-workshop period, indicating that digital marketing strategies have a positive impact on participants' competitiveness and income. Some participants were even able to develop Lata yam-based processed products, such as chips and yam flour, which have a higher selling value than raw products. This programme not only provides economic benefits for participants, but also has an impact on increasing community motivation and confidence in developing local products. This workshop is expected to be the first step in creating a sustainable marketing ecosystem, where communities can independently develop and market their local products more effectively. Through continued support and further training, it is hoped that Lata yam can become one of the leading commodities that is widely recognised, both in the national and international markets, so as to be able to make a long-term contribution to local economic development.